The moderate‐intensity continuous exercise maintains renal blood flow and does not impair the renal function. Issue 15 (4th August 2022) - Kawakami, Shotaro; Yasuno, Tetsuhiko; Kawakami, Saki; Ito, Ai; Fujimi, Kanta; Matsuda, Takuro; Nakashima, Shihoko; Masutani, Kosuke; Uehara, Yoshinari; Higaki, Yasuki; Michishita, Ryoma
Abstract: Exercise is restricted for individuals with reduced renal function because exercising reduces blood flow to the kidneys. Safe and effective exercise programs for individuals with reduced renal function have not yet been developed. We previously examined the relationship between exercise intensity and renal blood flow (RBF), revealing that moderate‐intensity exercise did not reduce RBF. Determining the effects of exercise duration on RBF may have valuable clinical applications. The current study examined the effects of a single bout of continuous exercise at lactate threshold (LT) intensity on renal hemodynamics. Eight adult males participated in this study. Participants underwent 30 min of aerobic exercise at LT intensity using a cycle ergometer. Evaluation of renal hemodynamics was performed before and after exercise, in the recovery phase using ultrasound echo. Furthermore, blood and urine samplings were conducted before and after exercise, in the recovery phase. Compared with resting, RBF was not significantly changed immediately after continuous exercise (319 ± 102 vs. 308 ± 79 ml/min; p = 0.976) and exhibited no significant changes in the recovery phase. Moreover, urinary kidney injury molecule‐1 (uKIM‐1) level exhibited no significant change immediately after continuous exercise (0.52 ± 0.20 vs. 0.46 ± 0.27 μg/g creatinine; p = 0.447). In addition, the results revealed no significant change in urinary uKIM‐1 in 60‐min after exercise. Other renal injury biomarkers exhibited a similar pattern. These findings indicate that a single bout of moderate‐intensity continuous exercise maintains RBF and does not induce renal injury.